The current state of the cenopopulations of Adonis tianschanica (Adolf) Lipsch. (Ranunculaceae) in Southeast Kazakhstan - KANAT KULYMBET; NASHTAY MUKHITDINOV; SERIK KUBENTAYEV; KURALAY TYNYBAYEVA; ASEM TASTANBEKOVA; MERUYERT KURMANBAYEVA; YUSUFJON GAFFOROV; RAUSHAN KAPARBAY; MOLDIR ZHUMAGUL (Society for Indonesian Biodiversity, 2023)
Abstract. Kulymbet K, Mukhitdinov N, Kubentayev S, Tynybayeva K, Tastanbekova A, Kurmanbayeva M, Gafforov Y, Kaparbay R, Zhumagul M. 2023. The current state of the cenopopulations of Adonis tianschanica (Adolf) Lipsch. (Ranunculaceae) in Southeast Kazakhstan. Biodiversitas 24: 4359-4372. Adonis tianschanica (Adolf) Lipsch. is a rare, sub-endemic species growing in the Tien Shan mountains with declining numbers, making it listed in the Red Book of Kazakhstan. The aim of the study is to investigate the distribution and abundance of A. tianschanica cenopopopulations (CP) in its natural habitats in southeastern Kazakhstan as well as assess soil characteristics, biological and arealogical features, including the ontogenetic structure of cenopopopulations. Five cenopopulations (CP) of A. tianschanica were identified, namely two CPs in Ketmen Ridge (Kegen Pass), two CPs in Dzungarian Alatau (Tekeli Gorge) and one CP in Terskey Alatau (Saryzhaz). Vegetation data were collected using the traditional methods of field geobotanical studies based on the ecological-physiognomic approach.Plant communities having dominant species from a single ecobiomorph and ecologically related species groups.We complemented the population analysis with a soil properties map compiled from existing cartographic and available literature. The results of this study indicated the low number of A. tianschanica individuals in all CPs, which is likely due to the biological characteristics of the species (i.e. low seed production and seedling recruitment and the lack of vegetative regeneration) as well as environmental factors, and anthropogenic impact, mainly grazing with. We found that the total number of individuals of A. tianschanica in the five cenopopulations was 106 individuals. The average density of the species varied from 1.3 to 3.1 plants/m2 with CP2 being the highest and CP5 the lowest. The five cenopopulations were classified based on the absolute maxima of ontogenetic groups. There were two maxima in the age composition of individuals in CPs 3 and 4: the first (18.8-42.1%) was a group of vegetative plants (v), and the second (21.1-50.0%) was a group of young generative plants (g1). The natural state of the habitat of this cenopopulation can be explained as more favorable than others. In CP2, the absolute maximum corresponded to vegetative plants group (v) (37.0%). In CP5, young generative individuals (g1) and mature generative (g2) predominated (from 30.8% to 38.4%). In terms of age composition, the state of A. tianschanica cenopopulations is considered relatively satisfactory but demonstrated a low level of abundance. It has been established that the state of the species populations in the studied regions is affected by soil conditions, changes in climatic conditions and anthropogenic impact.